The relationship between hypernatremia and breast milk sodium levels in newborns with hypernatremic dehydration - Tekin Orgun, Leman; Atlıhan, Fusün; Olukman, Özgür; İşleten, Figen; Orgun, Ali; Genel, Ferah; Çalkavur, Şebnem; Öztürk, İsmail Cengiz; Özbek, Erhan (The European Research Journal, 2019)
Objectives: Breast-feeding with high sodium content milk may cause hypernatremic dehydration in neonates (NHD). The number of cases with NHD tends to increase particularly in the higher temperature seasons. In this prospective case-control study, the relationship between NHD and breast milk sodium (Na) levels and demographic features of NHD were investigated during the summer season. Methods: The study included term newborns admitted to the neonatal intensive care unit of our hospital with the diagnosis of hypernatremic dehydration between June 2009 and October 2009. Serum sodium level ≥ 150mEq/L was accepted as hypernatremia. Among 109 NHD patients, breast milk sodium level was evaluated in 50 cases. Term infants without hypernatremic dehydration were taken as the control group (50 cases). Results: Postnatal age at admission ranged between 2 and 12 days and mean serum Na concentration was 152 mEq/L (150-173 mEq/L). A significant weight loss of >10% was determined in 85% of cases. Breast milk Na was significantly higher in the hypernatremic group (24.3 ± 20.3 mEq/L) compared to the control group (12.6 ± 6.79 mEq/L) (p < 0.001). In primiparous mothers, the mean breast milk Na level was statistically higher than that of multipara mothers (21.16 ± 19.9 mEq/L vs 15.48 ± 9.96 mEq/L, p < 0.016). Conclusions: In this study, we demonstrated that high breast milk sodium level was closely related with NHD and being a primiparous mother appeared as a significant factor for high breast milk sodium content. In this respect, all pregnant women especially primiparous should be educated about infant nutrition and neonatal dehydration. Health care providers should emphasize importance of frequent milking and more fluid intake, especially in summer.